2015
DOI: 10.5935/0101-2800.20150070
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-induced nephropathy after primary angioplasty for acute myocardial infarction

Abstract: Nefropatia induzida por contraste após angioplastia primária no infarto agudo do miocárdio Contrast-induced nephropathy after primary angioplasty for acute myocardial infarctionIntrodução: A prevenção da nefropatia induzida por contraste (NIC) é difícil nas situações de emergência, tornando essenciais estudos sobre NIC em pacientes submetidos à angioplastia de urgência. Objetivo: Determinar a incidência e fatores associados à NIC em pacientes com infarto agudo do miocárdio (IAM) submetidos à angioplastia nas p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
0
15
2
1
Order By: Relevance
“…The incidence of CIN varies greatly after coronary angiography and may be as low as 6% in patients undergoing elective catheterization [12]. The incidence of CIN in the study of Tziakas et al [13] was about 16% in both elective and urgent catheterization, and it reached 25% in urgent catheterization [14]. Mehran et al [15] showed that the overall occurrence of CIN in 8,357 patients was 13.1%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of CIN varies greatly after coronary angiography and may be as low as 6% in patients undergoing elective catheterization [12]. The incidence of CIN in the study of Tziakas et al [13] was about 16% in both elective and urgent catheterization, and it reached 25% in urgent catheterization [14]. Mehran et al [15] showed that the overall occurrence of CIN in 8,357 patients was 13.1%.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unlikely that contrast media is the sole factor responsible for AKI in the patients undergoing PCI. Conditions resulting in hypotension, hemodynamic instability, or cardiogenic shock and acute heart failure are additional contributing factors that may lead directly to AKI or potentiate the effects of contrast media [14]. Consequently, in the setting of PCI, most AKI events likely have alternative and multiple etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast-induced nephropathy after primary angioplasty for acute myocardial infarction/Santos et al/2015/Brazil/ J Bras Nefrol (19) .…”
Section: Cohort/levelmentioning
confidence: 99%
“…CIN is defined as increase in serum creatinine level by ≥0.5 mg/dl above the admission value or a >25% relative rise during the first 72 hours after the procedure [12]. The incidence of CIN after PPCI is increasing due to the emergency condition, as there is no time for implementation of prophylactic measures against CIN in high-risk patients and dealing with hemodynamic compromise [13].…”
Section: Introductionmentioning
confidence: 99%